Principal's Strategy in Optimizing Teacher Performance Through Discipline - Erwin Syamsudin, Erwin Syamsudin (Universitas Pahlawan Tuanku Tambusai, 2026)
Teacher discipline is a fundamental determinant of school effectiveness. Yet, a significant gap often exists between normative standards and actual compliance, where technical-punitive measures fail to address complex adaptive challenges. Based on the case at SMAIT Al-Kautsar Pondok Cabe, this study analyzes the Principal's strategy in optimizing teacher performance through discipline. Employing a qualitative descriptive method, data were collected via observations and interviews with nine informants. The findings reveal that a hybrid strategy—integrating moral legitimacy, systemic supervision, and situational engineering—successfully transformed the culture from conditional compliance to professional order. Notably, the Mandatory Reading Program effectively locked attendance through social conformity rather than fear. However, success remains heavily correlated with the principal's paternalistic influence and personal power. The study concludes that while hybrid strategies are effective, long-term sustainability requires shifting from external control to the internalization of professional values.